Analisis Communitization dalam Platform Social reading di Indonesia - Fani Nur Jannah; Amalia Rizky Fatonah; Maida Turnip (Jurnalistik dan Media, 2024)
The concept of social reading as a community platform for book readers emerged as the adoption of information technology in the field of book and ebook publishing. Where, this platform appears as a place between writers, readers, and publishers to interact with each other. Even since the covid-19 pandemic, the development of social reading platforms has been growing rapidly. This can be seen from the many similar platforms that have appeared during the pandemic. In this article, the author wants to analyze the communitization concept which is part of the new wave marketing in the development of social reading in Indonesia. By using a qualitative approach based on the constructivist paradigm and the case study method, this research raises several findings. Among other things, if the emergence of a social reading platform indirectly makes it easier for writers and publishers to find their target market, communicate interactively with them, and carry out a good marketing communication strategy. With the nature of horizontal interaction between them and the existence of technology as a medium, this is in accordance with the communitization aspect of New Wave Marketing.